FORMATION OF CONTINUOUS EDUCATION SYSTEM ON THE BASIS OF SUSTAINABLE DEVELOPMENT: PROJECT ACTIVITY EXPERIENCE - Ridei, Nataliia; Tymoshenko, Valentyna; Slabetsky, Alexander (Педагогічна освіта: теорія і практика, 2020)
The research work analyzes the functional orientation of sustainable development strategy studies. It suggests basic didactic and pedagogical conditions for innovativeness of the educational process and develops a set of subject-specific competencies. The study outlines the system architectonics for organizing the educational and research work in professional training of students. It develops research methods and methodology for professional training of specialists including recommendations of scientific-methodological, organizational-pedagogical and organizational-managerial nature. The main idea of the research lies in the development and implementation of theoretical-methodological foundations for shaping the system of continuous education based on the concept of sustainable development, with consideration of interests of the Ukrainian society evolving within the framework of sustainable development; restructuring of the postgraduate education system and, in particular, realizing potential pedagogical opportunities that determine selection of the most effective forms of training in the postgraduate education system. The practical value of the research lies in the fact that the obtained and presented results enable further integrated and sectoral development of various aspects in theory of education and create a methodological basis for building effective models of quality assurance in higher education. This research deepens the traditional views of scientific works on the problems of modernizing professional teacher training in the conditions of cross-border integration of social and cultural forms of education. Introduction of the system to form scientific-methodological competence in postgraduate pedagogical education; the results we have obtained, presented, and proven contribute to the implementation of individualized educational and scientific programs of teachers’ professional training; the results can be of practical use for a wide range of postgraduate education specialties in formation and development of legal competence in higher education administrators; the informational studentoriented portable environment of psycho-pedagogical training can be used in further research on development of higher education for future vocational school teachers, in determining regularities of its work, ways and directions to improve and enhance the effectiveness of their psycho-pedagogical training, as well as for adult education, for writing term papers and qualifying papers, textbooks, monographs, dissertations; these materials can be used in the higher education institutions of various types that are engaged in training environmental protection specialists in environmental monitoring, as well as in postgraduate education to ensure implementation of the government’s environmental policy. Introduction of the system to form scientificmethodological competence in postgraduate pedagogical education; these materials can be used in the higher education institutions of various types that are engaged in training environmental protection specialists in environmental monitoring, as well as in postgraduate education to ensure implementation of the government’s environmental policy.